The Problems of Controlling the Transparency of the Financial Budget Use of Corona Virus 19 - Lego Karjoko; I Gusti Ayu Ketut Rachmi Handayani; Abdul Kadir Jaelani (Faculty of Law, Universitas Sebelas Maret, 2020)
This study aims to analyze and illustrate the problem of monitoring the transparency of the use of the Corona Virus 19 financial budget. Transparency is one of the important elements in the realization of good governance. This research is a normative study with a statutory approach. The data of this research uses secondary data with primary, secondary and tertiary legal materials. The results show that first, the Covid-19 pandemic has caused a decline in the economy and activities in various sectors. Second, supervision of the use of covid funds is very weak considering Law Number 2 of 2020 gives absolute power to change budget postors and remove checks and balances and gives immunity authority to the government in managing state finances so that they cannot be corrected and are immune to the law.